Pancreatic adenocarcinoma third line systemic treatments: a retrospective cohort study - A. Gueiderikh; A. Tarabay; M. Abdelouahab; C. Smolenschi; M. L. Tanguy; M. Valery; D. Malka; T. Pudlarz; A. Fuerea; V. Boige; A. Hollebecque; M. Ducreux; et al. (BMC Cancer, 2024)
Abstract Background Chemotherapy for metastatic pancreatic adenocarcinoma (PDAC) primarily relies on FOLFIRINOX (LV5FU- irinotecan – Oxaliplatine) and Gemcitabine – Nab-Paclitaxel in the first-line setting. However, second-lines remain less well-defined and there is limited data regarding third-line treatments. The objective of our study was to determine the proportion of patients advancing to third line chemotherapy, to outline the various third-line chemotherapy regimens used in routine practice and to evaluate their respective efficacy. Methods A retrospective single-center cohort from 2010-2022 compiled baseline characteristics, treatment outcomes and survival of PDAC patients who received at least one chemotherapy line in a French tertiary-center. Overall survivals (OS) were analyzed using a Cox multivariable model. Results In total, 676 patients were included, with a median follow-up time of 69.4 months, (Interquartile Range (IQR) = 72.1). Of these, 251 patients (37%) that proceeded to 3rd-line chemotherapy. The median PFS in 3rd line was 2.03 months, [CI95%: 1.83, 2.36]. The median 3rd line overall survival was 5.5 months, [CI95%: 4.8, 6.3]. In multivariable analysis erlotinib-based chemotherapy was found to be deleterious (HR=2.38, [CI95%: 1.30, 4.34], p=0.005) compared to fluoropyrimidine-based chemotherapy in terms of 3rd line overall survival while gemcitabine monotherapy showed a tendency towards negative outcomes. First and 2nd line chemotherapies sequence didn’t influence 3rd line outcome. Conclusion In our cohort, one-third of treated patients proceeded to 3rd line chemotherapy resulting in a 5.5 months median 3rd line OS, consistent with treatments at advanced stage. Our results argue against the use of erlotinib and gemcitabine monotherapy.